2013
DOI: 10.4103/0971-4065.120340
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of spot urine protein creatinine ratio in measuring proteinuria in chronic kidney disease stage 3 and 4

Abstract: We studied the accuracy of spot urine protein creatinine ratio (SpUr-PCR) to assess 24 h urine protein excretion (24 h-UP) in patients with chronic kidney disease (CKD). A total of 100 proteinuric CKD patients of stages 3 and 4 were studied. 24 h urine was collected to measure 24 h-UP and creatinine. A random day time urine sample was analyzed to measure the PCR. A formula to estimate 24 h creatinine excretion was derived from linear regression analysis and a correction factor was introduced to assess whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Studies restricted to patients with chronic kidney disease and diabetic nephropathy have also shown weaker correlations in patients with nephrotic range proteinuria. 22, 23 …”
Section: Discussionmentioning
confidence: 99%
“…Studies restricted to patients with chronic kidney disease and diabetic nephropathy have also shown weaker correlations in patients with nephrotic range proteinuria. 22, 23 …”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have reported disagreement between 24UP and PCR depending on gender in smaller populations [24,26]. Nayak et al [26] studied 100 patients (81 men and 19 women) with CKD and provided a correction factor for creatinine excretion that minimized disagreement between 24UP and PCR in females [26]. However, our study is the first to provide and validate an equation to estimate 24UP directly from PCR in a large Caucasian population adjusting for gender.…”
Section: Discussionmentioning
confidence: 70%
“…As a general rule, it is therefore expected that patients with large body sizes will exhibit lower PCR than 24UP values [25]. Furthermore, the difference in muscular mass between males and females also suggests that assessment of proteinuria by means of the PCR could be subjected to a gender bias, as earlier described in other ethnic groups [26] and for microalbuminuria [27,28,29]. …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The renal impairment was characterized in HSF group by the increased protein/creatinine ratio and albuminuria. Total proteinuria (represented by the protein/creatinine ratio) and albuminuria are important markers of kidney damage used as prognostic indicators in patients with chronic kidney disease [50]. Moreover, albuminuria is likely a reflection of early damage to the glomerular vascular endothelium as well as decreased ability of the tubule to reabsorb urinary albumin [51].…”
Section: Discussionmentioning
confidence: 99%